Upaya Meningkatkan Kemampuan Bahasa Anak Melalui Kartu Huruf Di Tk Bahari Kofarkor - Uspessy, Mayling Ketrin; Rokhima, Nur; Ardiansyah, Fuad (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
As a means of communication, language is a very important tool in children’s lives. Language is also a tool for conveying thoughts and feelings to other people which also functions to understand other people’s thoughts and feelings. The aim of developing early childhood language skills is so that students are able to communicate verbally with their environment. This is in contrast to the situation at the Bahari Kofarkor Kindergarten, Raja Ampat Regency, where many children are not able to speak the language well and are not able to receive the language well either. For example, children cannot carry out 2-3 commands spoken by the teacher, children cannot tell simple experiences, etc. So this research was done. With the aim of improving children’s language skills through role-playing activities. This research consists of two cycles where the previous activities were carried out. Research (pre cycle) the average language ability of children was only 30.46% or as many as 6 out of 15 children. In cycle I it was 50.46%. Meanwhile in cycle II children’s language skills had increased on average. Average of 70.23%. Thus it can be said that the role of Letter Card activities can improve children’s language skills at the Bahari Kofarkor Kindergarten and parents are expected to provide the right stimulus for each level. Development so that the child’s growth and development can be achieved optimally.